2020
DOI: 10.1088/1755-1315/441/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of marine fish freshness based on the handling method in Puncak Permai modern market and Simo Gunung traditional market, Surabaya

Abstract: Fish handling conditions on the market nowadays mainly in the traditional market is less a principle handling with caution, fast, and clean, making the selling fish polluted with chemical, physical, and microbiological pollutants. The fish handling on the modern market is generally better than the traditional markets. Puncak Permai and Simo Gunung Market provide fresh fish more than any other market in Surabaya, making these markets become the main destination for consumers, therefore this study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The following table shows the results of testing the pH of swanggi fish at TPIBrondong. The pH value is one of the indicators used to determine the level of freshness of fish and is closely related to the process of quality reduction [12]. Testing the degree of acidity (pH) of swanggi fish using a pHmeter.…”
Section: Swanggi Fish Phmentioning
confidence: 99%
“…The following table shows the results of testing the pH of swanggi fish at TPIBrondong. The pH value is one of the indicators used to determine the level of freshness of fish and is closely related to the process of quality reduction [12]. Testing the degree of acidity (pH) of swanggi fish using a pHmeter.…”
Section: Swanggi Fish Phmentioning
confidence: 99%
“…For the Indonesia's crab export performance to rise and return to a positive trend, it is vital to develop markets for potential countries and increase the production of products that have added value. The Indonesian government under the Ministry of Maritime Affairs and Fisheries (MMAF) Research and Human Resources Agency has issued various policies related to crab marketing patterns, one of which is to increase the market reach of crab products (Sari et al, 2020). Yusuf et al (2021) reported that a more comprehensive and integrated business, such as market diversification to the ASEAN region is up-and-coming and has good economic opportunities after the Covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%